2020
DOI: 10.38212/2224-6614.1267
|View full text |Cite
|
Sign up to set email alerts
|

Nanomaterial-based fluorescent biosensor for veterinary drug detection in foods

Abstract: Veterinary drugs have been widely used in the food industry. Their residues in food products need to be tightly regulated to ensure food safety. In particular, some veterinary drugs are still used illegally, although they have already been banned. Nanomaterials are playing an increasingly important role in analytical chemistry due to their unique properties. Compared to traditional organic dyes and colloidal gold nanoparticle labels, fluorescent nanomaterials appear particularly attractive for the detection of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
20
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 24 publications
(20 citation statements)
references
References 104 publications
(150 reference statements)
0
20
0
Order By: Relevance
“…They may provide enough sensitivity for detection of food contaminants, but problems are usually raised when the matrix is complex. To further improve sensitivity, nanomaterials such as gold nanoparticles, silver nanoparticles, and gold nanoclusters have been used to ensure food safety (Han et al, 2020;Tao et al, 2020). When new or unknown pesticides, insecticides, or bacterial variants are present, standard approaches usually do not work.…”
Section: Food Safetymentioning
confidence: 99%
“…They may provide enough sensitivity for detection of food contaminants, but problems are usually raised when the matrix is complex. To further improve sensitivity, nanomaterials such as gold nanoparticles, silver nanoparticles, and gold nanoclusters have been used to ensure food safety (Han et al, 2020;Tao et al, 2020). When new or unknown pesticides, insecticides, or bacterial variants are present, standard approaches usually do not work.…”
Section: Food Safetymentioning
confidence: 99%
“…Biosensors are a promising approach, since they combine the high selectivity of biorecognition elements, either natural (e.g., antibodies) or synthetic (e.g., aptamers or imprinted polymers), with simple preanalytical and analytical procedures [ 3 , 4 , 5 , 6 , 7 ]. Portable biosensors are ideal for food safety applications, as attested by several works reported in the literature for the detection of pathogens [ 8 , 9 ], toxins [ 10 , 11 ], pesticides and veterinary drug residues [ 12 , 13 ], organic pollutants [ 14 , 15 ], and allergens [ 16 ].…”
Section: Introductionmentioning
confidence: 99%
“… 22 In recent years, QDs have attracted extensive attention and greatly promoted the development of fluorescence immunoassay. 23 In particular, it was found that QDs modified with different surface functional groups exhibited photoluminescence or chemiluminescence response to external stimulation, indicating their excellent sensing potential. 24 Fluorescence correlation detection technology is becoming high-profile and also show prospects in the field of veterinary drug residue detection.…”
Section: Introductionmentioning
confidence: 99%